Work-related health in Europe: are older workers more at risk? - Jones, Melanie K.; Latreille, Paul L.; Sloane, Peter J.; Staneva, Anita V. (Bonn, 2011)
"This paper uses the fourth European Working Conditions Survey (2005) to address the impact of age on work-related self-reported health outcomes. More specifically, the paper examines whether older workers differ significantly from younger workers regarding their job-related health risk perception, mental and physical health, sickness absence, probability of reporting injury and fatigue. Accounting for the 'healthy worker effect', or sample selection – in so far as unhealthy workers are likely to exit the labour force – we find that as a group, those aged 55-65 years are more 'vulnerable' than younger workers: they are more likely to perceive work-related health and safety risks, and to report mental, physical and fatigue health problems. As previously shown, older workers are more likely to report work-related absence."